The Use of Human Epididymis 4 and Cancer Antigen 125 Tumor Markers in the Benign or Malignant Differential Diagnosis of Pelvic or Adnexal Masses - (:unkn) unknown (GALENOS YAYINCILIK, 2017)
Background: Ovarian cancer is one of the highest mortality cancers in gynaecology. Discrimination of benign masses from malignant ones may sometimes become a challenge for the clinician since there is not a reliable tumour marker, thus some unnecessary, highly morbid operations can be performed. Aims: To explore the efficacy of human epididymis 4 (HE 4) and cancer antigen 125 (CA 125) markers in differentiating malignant and benign pelvic masses of ovarian origin and to identify the cut-off points for those markers. Study Design: Prospective study. Methods: Fifty-one patients who were diagnosed and planned to undergo surgery for ovarian mass between June 2008 and December 2008 were enrolled into this study. Preoperative venous blood samples were taken and frozen for marker investigation and final diagnoses were concluded by histopathological examination. After recruitment of all cases CA 125 and HE 4 levels were evaluated. Results: The statistical analysis did not indicate any statistically significant difference between the CA 125 levels of the patients with malignant and benign adnexal masses (p=0.105). The HE 4 levels of the patients with malignant adnexal masses were higher at a statistically significant level compared to the patients with benign adnexal masses (p=0.002). For HE 4 tumour marker and at the cut-off point of > 25 pM, sensitivity was 1, specificity 0.40, positive cut-off value 0.19, negative cut-off value 1, accuracy 0.47 and positive likelihood ratio 1.65. Conclusion: Human epididymis 4 is a better diagnostic tool than CA 125 in benign-malignant discrimination of adnexal masses. The cut-off value of 25 pmol/L for human epididymis 4 will contribute to providing proper guidance to patients with adnexal masses and applying the proper treatment method.
Keywords: Tumour marker; ovarian cancer; adnexal mass; human epididymis 4; cancer antigen 125; EPITHELIAL OVARIAN-CANCER; HE-4; PROTEIN; CARCINOMA; ALGORITHM; CA125; SYMPTOMS; MULTIPLE; RISK; ROMA